Policy and Politics of Preference of Admin Cadre in the Bangladesh Civil Service: Consequences - Karim, Mohammad Razaul (Journal of Public Administration and Government, 2025)
Bangladesh's administrative cadre implements government policies and projects, giving them significant power. Administrative cadre preference throughout several sectors depletes specialised expertise in education, healthcare, construction, agriculture, and livestock. This study aims to improve understanding of the Bangladesh Civil Services (BCS) administrative and technical cadres' differing concerns and their societal and national ramifications. The researcher conducted a qualitative interview-based study to address these concerns. Compared to the administrative cadre, the technical cadre is demotivated by long promotion processes, limited fringe benefits, lost status, and poor working conditions. This study suggests that the BCS admin cadre's dominance hurts public administration efficiency and effectiveness.